Conjugal Transfer of the blaCTX-M-1 Gene Between Escherichia coli and Salmonella enterica serovar Enteritidis in Seafood - Abdulla, Mohamed Hatha; Sukumaran , Divya P; Joshy, Sithara; Poulose, Jismol; Christy, Angel Benita; Antony, Ally C; Sivan, Gopika (Fishery Technology, 2025)
The aim of the present study was to investigate the conjugal transfer of the blaCTX-M-1 gene from Escherichia coli to E. coli and from E. coli to Salmonella enteritidis serovar Enteritidis in Villorita cyprinoides and Penaeus monodon at different temperatures. An E. coli strain (N13) harbouring the blaCTX-M-1 gene was used as the donor strain. The recipients were E. coli (EF2) and S. Enteritidis (S3), both nalidixic acid-resistant strains of shellfish origin. Antibiotic susceptibility testing, minimum inhibitory concentration (MIC) determination and PCR detection of the blaCTX-M-1 gene were performed to verify transconjugants. The clonal relationships between donors, recipients and transconjugants were assessed using ERIC-PCR. The results indicated that transfer frequency was highest at 30°C and lowest at 42°C for both mating pairs (N13-EF2 and N13- S3) in V. cyprinoides and P. monodon. Both pairs (N13-EF2 and N13-S3) exhibited higher transfer frequencies in V. cyprinoides than in P. monodon. This study demonstrates that conjugation is a significant factor in the rapid dissemination of beta-lactam resistance among foodborne pathogens and highlights the potential risk of contaminated seafood as a transmission route of the blaCTX-M-1 gene to consumers.